Semantic interoperability in multi-cloud platforms: a reference architecture utilizing an ontology-based approach - Hamdan, Norazian M.; Admodisastro, Novia; Osman, Hafeez; Muhammad, Muhammad Sufri (Insight Society, 2024)
The rapid expansion of cloud computing has necessitated the development of multi-cloud strategies, which leverage the strengths of multiple cloud service providers to mitigate risks such as vendor lock-in and enhance performance and reliability. Nevertheless, semantic interoperability remains a critical challenge in multi-cloud platforms, where diverse cloud services need to communicate and function seamlessly. Current solutions lack a unified semantic-based representation within reference architectures in multi-cloud platforms and mainly focus on the independent interoperability of a service model, i.e., SaaS, PaaS, and IaaS. This study addresses the critical issue of semantic interoperability in multi-cloud platforms, where the heterogeneity of proprietary cloud solutions impedes seamless integration and communication. Thus, we proposed a reference architecture utilizing an ontology-based approach to facilitate semantic interoperability across diverse cloud platforms. The reference architecture is based on five semantic interoperability requirements identified in our previous study. This paper presents the design and development of a reference architecture that includes high-level and low-level components supported by a taxonomy of semantic interoperability in multi-cloud platforms. Expected outcomes of this study include a standardized framework using an ontology-based approach for semantic mapping and integration of cloud services, which will significantly enhance interoperability and efficiency in multi-cloud platforms. The significance of this research lies in its potential to advance the state of knowledge and practice in multi-cloud computing, enabling more robust and flexible cloud service ecosystems.